Circulating Free Methylated Tumor DNA Markers for Sensitive Assessment of Tumor Burden and Early Response Monitoring in Patients Receiving Systemic Chemotherapy for Colorectal Cancer Liver Metastasis. Issue 5 (November 2018) - Bhangu, Jagdeep Singh; Beer, Andrea; Mittlböck, Martina; Tamandl, Dietmar; Pulverer, Walter; Schönthaler, Silvia; Taghizadeh, Hossein; Stremitzer, Stefan; Kaczirek, Klaus; Gruenberger, Thomas; Gnant, Michael; Bergmann, Michael; et al.
Abstract : Background: Neoadjuvant chemotherapy (neoCTx) followed by hepatic resection is the treatment of choice for patients with colorectal cancer liver metastasis (CLM). Treatment response is generally assessed using radiologic imaging after several cycles of chemotherapy. However, earlier assessment of response would be desirable since nonresponders could be switched early to an alternative chemotherapy regimen. Recent evidence suggests that circulating free methylated tumor DNA is a highly sensitive biomarker and may more accurately reflect tumor burden and treatment response than conventional markers for CRC. Patients and Methods: Thirty-four patients with CLM who received neoCTx prior to intended hepatic resection were included in this prospective nonrandomized study. Peripheral blood plasma was collected at baseline and before each cycle of neoCTx and was then analyzed for aberrant methylation of 48 CRC-associated genes. Methylation marker levels were correlated with baseline tumor volume and treatment response and compared with the standard tumor markers CEA and CA 19-9. Results: The methylation markers SEPT9, DCC, BOLL, and SFRP2 were present in all patients at baseline and displayed a stronger correlation with tumor volume than CEA and CA 19-9. Serial measurement of these methylation markers allowed for discrimination between operated and nonoperated patients already after 1 cycle of neoCTx with high sensitivity and specificity. The early dynamic changes of SEPT9 and DCC also seemed to correlate with pathohistological response. Conclusion: Our data suggest that serial measurements of CRC-associated methylation markers could be a particularly valuable tool for early response assessment in patients receiving neoCTx for CLM.